Dehumanization During the COVID-19 Pandemic - Markowitz, David M.; Shoots-Reinhard, Brittany; Peters, Ellen; Silverstein, Michael C.; Goodwin, Raleigh; Bjälkebring, Pär (Frontiers in Psychology, 2021)
Communities often unite during a crisis, though some cope by ascribing blame or stigmas to those who might be linked to distressing life events. In a preregistered two-wave survey, we evaluated the dehumanization of Asians and Asian Americans during the COVID-19 pandemic. Our first wave (March 26–April 2, 2020; N=917) revealed dehumanization was prevalent, between 6.1%-39% of our sample depending on measurement. Compared to non-dehumanizers, people who dehumanized also perceived the virus as less risky to human health and caused less severe consequences for infected people. They were more likely to be ideologically Conservative and believe in conspiracy theories about the virus. We largely replicated the results one month later in our second wave (May 6–May 13, 2020; N=723). Together, many Americans dehumanize Asians and Asian Americans during the COVID-19 pandemic with related perceptions that the virus is less problematic. Implications and applications for dehumanization theory are discussed.